Job characteristics and their effect on the intention to quit apprenticeship - Katja Seidel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
This paper investigates job characteristics that German training companies could use as a signal to apprentices to lower the quit intentions of apprentices and further to maximize their own probability to cover occurred net costs. Moreover, the results could also be used as policy implications to avoid unnecessary early contract cancellations and especially real dropouts. 10 questions about how important certain achievements are to apprentices and how likely it is to achieve them, were used. For this the "BIBB Survey Vocational Training from the Trainees Point of View 2008" conducted by the Federal Institute for Vocational Education and Training (BIBB) is used. It is a representative German firm-level study of 5901 apprentices in 6 German federal states in the year 2008. The probit regressions show positive effects for job characteristics that represent job security. Expecting to be retained after the apprenticeship and encouraging apprentices to train further constantly decrease the intention to quit. Further, it seems that women are more affected by job security signals, but they also sort more often into occupations with lower retention probabilites. Consequently, it is more a indication for occupational segregation than a sign for differences between sexes.
Keywords: J24; J28; J30; 330; apprenticeship; quits; job characteristics; job satisfaction